Pengaruh Self Service Technology Terhadap Kepuasan Nasabah Pengguna Layanan Digital Bank Pada Bank Syariah Indonesia KCP Palembang Simpang Patal - Lestari , Echa; Walian , Armansyah; Lemiyana, Lemiyana (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the influence of Automatic Teller Machine/ATM, Mobile Banking, Internet Banking and Self Service Technology on customer satisfaction at Bank Syariah Indonesia KCP Palembang Simpang Patal.The reason behind the author's interest in writing this thesis is based on the researcher's sense of suggestion regarding the lack of customer understanding regarding technology, obstacles in using ATMs or Mobile Banking applications and Internet Banking which carry out transactions via cellphones, this is thought to be a lack of potential for improving Self Service Technology services in banks. Indonesian Sharia KCP Palembang Simpang Patal.This type of research is field research obtained directly through distributing questionnaires to BSI KCP Palembang Simpang Patal customers. The technique used in sampling is the Slovin formula. The sample used in this research was 99 customers of Bank Syariah Indonesia KCP Palembang Simpang Patal. The type of data used is primary data. Data analysis techniques in this research consist of validity testing, reliability testing, classical assumption testing, hypothesis testing. Based on the results of the analysis, the Automatic Teller Machine variable has a positive and significant effect on customer satisfaction, Mobile Banking has a positive and significant effect on customer satisfaction, Internet Banking has a positive and significant effect on customer satisfaction, and Self Service Technology simultaneously has an effect on customer satisfaction.